Perspectives of M-EEG and fMRI data fusion - Sanchez-Bornot, J.M. (CRC Press, 2014)
Recently, brain imaging techniques have been developed by numerous efforts directed at multimodal data fusion, which seeks to combine high-temporal resolution information, as can be provided by electromagnetic-based techniques (M-EEG), with high-spatial resolution, as has been traditionally achieved by the use of hemodynamic-based neuroimaging methods such as positron emission tomography (PET) and functional magnetic resonance imaging (fMRI) 1. In particular, the EEG/fMRI fusion has been well known for more than a decade owing to the higher levels of information on brain activity that can be obtained by the simultaneous combination of these complementary modalities, and the significantly increasing capacities for carrying out these studies 2,3. Â© 2015 by Taylor & Francis Group, LLC.